2013
DOI: 10.1111/1462-2920.12278
|View full text |Cite
|
Sign up to set email alerts
|

Marked seasonality of aerobic anoxygenic phototrophic bacteria in the coastal NW Mediterranean Sea as revealed by cell abundance, pigment concentration and pyrosequencing of pufM gene

Abstract: The abundance and diversity of aerobic anoxygenic phototrophs (AAPs) were studied for a year cycle at the Blanes Bay Microbial Observatory (NW Mediterranean) and their potential links to an array of environmental variables were explored. Cell numbers were low in winter and peaked in summer, showing a marked seasonality that positively correlated with day length and light at the surface. Bacteriochlorophyll a concentration, their light-harvesting pigment, was only detected between April and October, and pigment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
83
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(98 citation statements)
references
References 70 publications
(157 reference statements)
15
83
0
Order By: Relevance
“…6). These findings are in agreement with results reported by Ferrera et al (2014), who found a defined seasonal pattern with summer maxima and winter minima both in AAP abundance and BChl a concentration. However, it must be kept in mind that we have presented BChl a data and not AAP abundances and therefore only tentative extrapolations can be made to describe AAP distribution considering that (1) per cell concentration of BChl a can be very variable and (2) a previous study in the Mediterranean Sea showed a highly significant correlation between pigment concentration and cell numbers (Lamy et al 2011).…”
Section: Dynamics Of Pigments Relevant To Photoheterotrophysupporting
confidence: 94%
See 1 more Smart Citation
“…6). These findings are in agreement with results reported by Ferrera et al (2014), who found a defined seasonal pattern with summer maxima and winter minima both in AAP abundance and BChl a concentration. However, it must be kept in mind that we have presented BChl a data and not AAP abundances and therefore only tentative extrapolations can be made to describe AAP distribution considering that (1) per cell concentration of BChl a can be very variable and (2) a previous study in the Mediterranean Sea showed a highly significant correlation between pigment concentration and cell numbers (Lamy et al 2011).…”
Section: Dynamics Of Pigments Relevant To Photoheterotrophysupporting
confidence: 94%
“…Prokaryotic photoheterotrophs are divided into 3 main groups: aerobic anoxygenic phototrophic bacteria (AAPs), proteorhodopsin-containing bacteria (PR) and aerobic oxygenic phototrophic cyanobacteria dis playing heterotrophic-like behaviour (Béjà & Suzuki 2008). AAPs are known to generally represent less than 10% (though occasionally up to 25%; Lami et al 2007) of total prokaryotes in the marine photic layer (Lamy et al 2011, Ferrera et al 2014, PR have been estimated to represent up to 50% of the microorganisms living in the N orth Atlantic Ocean (Campbell et al 2008), and the contribution of Prochlorococcus to leucine uptake in the North Atlantic has been found to be up to 25% within the whole prokaryotic community (Mary et al 2008). Given the importance of these metabolic strategies, our view of carbon fluxes has dramatically changed over the past 15 yr (Gasol et al 2008, Ruiz-González et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…The ecological and biogeochemical implications of photoheterotrophic pathways are receiving increasing attention, and during the past decade there have been remarkable advances in our understanding of abundance and distribution patterns of AAP bacteria in lakes and oceans Ferrera et al, 2013;Fauteux et al, 2015). One of the main challenges in furthering our understanding of the ecological role of this group, and in particular in determining the scenarios where they may have an ecological advantage over their heterotrophic bacterial counterparts, has been determining the actual activity of these bacteria in situ.…”
Section: Discussionmentioning
confidence: 99%
“…Light availability would explain why AAP bacterial abundance is highest in the euphotic zone of the oceans and decreases with depth (Cottrell et al, 2006;Sieracki et al, 2006;Salka et al, 2008). Abundance of these bacteria also correlated with light intensity and day length over a year in Mediterranean coastal waters (Ferrera et al, 2014). We hypothesized that AAP bacteria would be more active than the rest of the bacterial community and that their activity would be enhanced by light.…”
Section: Introductionmentioning
confidence: 98%